2001
DOI: 10.1116/1.1418407
|View full text |Cite
|
Sign up to set email alerts
|

Can proximity x-ray lithography print 35 nm features? Yes

Abstract: We report on the results of our effort to extend proximity x-ray lithography (PXL) to 35 nm using a harder energy spectrum, and choosing the appropriate materials for the mask and the resist to match the transmission and absorption at higher energies. Previous studies [M. Kahn et al., J. Vac. Sci. Technol. B 17, 3426 (1999); T. Kitayama, J. Vac. Sci. Technol. B 18, 2950 (2000)] have shown that PXL is capable of printing 50 nm features, and in this study, we extend that work to show that PXL can indeed be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Kahn et al have evaluated Sicontaining resist and concluded that the Si-containing resist does not provide a great improvement in resolution but it still provides 2.5 times more absorption at 2.7 keV ͑4.6 Å͒ than UV5 resist. 4,5 Here, we study the electron stopping power and secondary electron blur in Br-containing resist. We also investigate the resolution in PXL and PXL-II.…”
Section: Introductionmentioning
confidence: 99%
“…Kahn et al have evaluated Sicontaining resist and concluded that the Si-containing resist does not provide a great improvement in resolution but it still provides 2.5 times more absorption at 2.7 keV ͑4.6 Å͒ than UV5 resist. 4,5 Here, we study the electron stopping power and secondary electron blur in Br-containing resist. We also investigate the resolution in PXL and PXL-II.…”
Section: Introductionmentioning
confidence: 99%
“…9 In the United States, The University of Wisconsin has been studying PXL-II, and they concluded that PXL has extendibility to 35 nm. 10,11 A thick diamond membrane, which gives high transmittance in harder spectra, is one of the key materials required to realize PXL-II. We have studied the application of diamond membranes to x-ray masks jointly with Mitsubishi Materials Corporation from the viewpoints of stiffness and resultant image placement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, other researchers 2,3 have achieved 50 nm resolution with PXL by using a 10 and 15 m gap between the mask and the wafer. Another study 4 shows that PXL can print 35 nm features using a higher energy radiation and smaller proximity gap ͑р5 m͒. Reducing the proximity gap to such a scale with standard masks however increases the risk of contact with the resist covered wafer during the positioning of the mask prior to exposure.…”
Section: Introductionmentioning
confidence: 99%